Crônicas de militância e cuidado às pessoas que fazem uso de drogas - Moura, Morgana Moreira (2019)
ABSTRACT Through chronicles, this paper presents the path of a PhD research whose objective was to follow the paths of the care and attention network of people who use drugs in Mato Grosso. In this sense, this text questions how harm reduction strategies are situated in this scenario and, more specifically, seeks to understand how public care policies are arranged, in the Cuiabano context, to identify practices that escape and provide rupture in the instituted and instituting models. and experimenting with inventive modes based on the hybrid Art-Psychology as a harm reduction strategy. Therefore, regarding the ontological and epistemological references that guide the work, it was supported by the schizoanalytical proposals and placed cartography as a methodological strategy, operationalized through an intervention research. Throughout the analysis process, there were theoretical articulations with anti-prohibitionist studies, studies on harm reduction and psychosocial attention, group processes and contemporary art. Finally, establishing an alliance between Contemporary Art and Psychology, he argues that therapeutic work in confluence with contemporary aesthetics is a strategy for empowering lives averse to the enclosing models of care offered to people who use drugs. The investigation process made it possible to visualize that, in the current conjuncture, it is necessary to build a care practice as militancy and a militancy as care. Militancy as a care is the construction of resistance processes guided by strangeness, so as not to accommodate what is normalized and, thus, to neglect. This form of militancy occurs in micropolitical practices or having public institutions or spaces as a possibility of creating militant contamination where power falls, dealing with modes of subjectivation connected with becomings and multiplicities, including as a strategy of resistance to academic writing. Already care as militancy seeks not to get used to the norms of health care, building practices and organizations that are inventive, that enhance lives. A care practice guided by the ethical-aesthetic-political paradigm, signaling the naturalizations that harden the territories, enabling the emergence of becomings, opening to the different, composing care in a micropolitical dimension.